General alternative regularization methods for split equality common fixed-point problem. (4th May 2018) - Zhao, Jing; Jia, Yunnuan; Zhang, Hang
Abstract: The purpose of this paper is to propose a general alternative regularization algorithm for split equality common fixed-point problem of nonexpansive operator in the framework of infinite-dimensional Hilbert spaces. We prove the strong convergence of the proposed algorithm with the stepsizes chosen by two ways. As a consequence, we obtain strong convergence theorems for split equality common fixed-point problem of firmly-nonexpansive operator and split equality problem. The efficiency of the proposed algorithms is illustrated by some numerical tests.